2022
DOI: 10.3390/cancers14215456
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy and Immunotherapy for Heterogeneous Breast Cancer

Abstract: Breast cancer (BC) is the most common malignancy in women worldwide, and it is a molecularly diverse disease. Heterogeneity can be observed in a wide range of cell types with varying morphologies and behaviors. Molecular classifications are broadly used in clinical diagnosis, including estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), epidermal growth factor receptor (EGFR), vascular endothelial growth factor receptor (VEGFR), and breast cancer gene (BRCA) mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 145 publications
0
13
0
Order By: Relevance
“…Adjuvant chemotherapy is the chemotherapy administered after surgery for BC patients with lymphatic metastases or high risk of suffering a recurrence (Early Breast Cancer Trialists' Collaborative et al, 2012). While chemotherapy applied to patients before operation is called neoadjuvant chemotherapy which determines the response of tumor to chemotherapy, lowers the tumor stage, and increases patient eligibility for breast conservation surgery, and it has important clinical value for locally advanced and inoperable BC (Wang and Mao, 2020;Davey et al, 2021;Sun et al, 2022).…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuvant chemotherapy is the chemotherapy administered after surgery for BC patients with lymphatic metastases or high risk of suffering a recurrence (Early Breast Cancer Trialists' Collaborative et al, 2012). While chemotherapy applied to patients before operation is called neoadjuvant chemotherapy which determines the response of tumor to chemotherapy, lowers the tumor stage, and increases patient eligibility for breast conservation surgery, and it has important clinical value for locally advanced and inoperable BC (Wang and Mao, 2020;Davey et al, 2021;Sun et al, 2022).…”
Section: Chemotherapymentioning
confidence: 99%
“…Apart from the risk of relapse, as a short-term solution, surgery also leads to long-term adverse effects such as anatomical changes, chronic pain, phantom breast pain, lymphedema and so on (Lovelace et al, 2019). Consistently, the radiotherapy can cause radiation dermatitis, radiation pneumonia, myelosuppression, cardiac and pulmonary injury, radiation-induced malignancy, fatigue, swelling and lymphedema and other side effects, interfering with activities of daily living (Lovelace et al, 2019;Sun et al, 2022).…”
Section: Obstacles Of Current Treatment Strategies Of Bcmentioning
confidence: 99%
“…Breast cancer (BC) represents one of the most common malignancies affecting women worldwide ( 1 ). Its lifetime risk development is associated with alterations in autosomal genes, including the well-known Breast Cancer gene 1 and 2, respectively BRCA1 and BRCA2 ( 2 ), which have a high penetrance in, the so-called, Hereditary Breast and Ovarian Cancer (HBOC) syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…2 Breast cancer treatment involves a variety of medications, including monoclonal antibodies and kinase inhibitors. 3,4 However, for triple-negative breast cancer (TNBC), therapeutic options are generally limited -2 targeted drugs are approved by the FDA (sacituzumab, govitecan, and pembrolizumab), but greater effectiveness is achieved when they are combined with conventional antitumor agents. 5 For cervical cancer treatment, there are no targeted agents yet.…”
Section: Introductionmentioning
confidence: 99%
“…34 Bian et al prepared four Au(III)-Schiff base complexes and found that all complexes expressed significant antiproliferative effects against hepatocellular carcinoma. 35 Abou-Melha reported a series of complexes of Cu(II), Co(II), Ni(II), and Zn(II) containing a new Schiff base ligand, N′-(benzo[d] [1,3]dioxol-5-ylmethylene)isonicotinohydrazide, and concluded that Cu(II) and Zn(II) complexes had the highest anti-cancer activity against hepatocellular carcinoma and ovarian cancer cell lines. 36 Three new Zn(II) and three Ni(II) complexes bearing dithiocarbazates Schiff base ligands have been prepared by Cavalcante et al The in vitro study of antitumor activity on MDA-MB-231 mammary carcinoma cells revealed an increased cytotoxic effect after complexation with Zn(II), in total contrast with the complexes of Ni(II), which were inactive.…”
Section: Introductionmentioning
confidence: 99%